Rethinking cybersecurity : strategy, mass effect, and states - Lewis, James Andrew, 1953- (Center for Strategic & International Studies ; Rowman & Littlefield, 2018)
Despite all the attention, cyberspace is far from secure. Why this is so reflects conceptual weaknesses more than imperfect technologies. Two questions highlight shortcomings in the discussion of cybersecurity. The first is why, after more than two decades, we have not seen anything like a cyber Pearl Harbor, cyber 9/11, or cyber catastrophe. The second is why, despite the increasing quantity of recommendations, there has been so little progress. This report explores these questions and assesses the accuracy of our perceptions of cybersecurity.